100 ways to change your life ebook The science of leveling up health, happiness, relationships & success. - Moody, Liz (2023)
**A USA Today bestseller!** **A Toronto Star bestseller!** From the creator of The Liz Moody Podcast comes a science-backed guide to creating your best life. What daily habits do happiness psychologists recommend to sprinkle our lives with joy? What does the latest research show about how we can live longer? How do the world's top gastroenterologists tackle bloating and constipation? How can we amp up our charisma, make and keep quality friendships, and overcome the burn out sapping our energy every day? 100 Ways to Change Your Life offers real answers to each of these questions, and so many more. This is a new kind of personal growth book; here, veteran journalist Liz Moody translates her years of experience interviewing the world's leading doctors, scientists, and thinkers into a smart, choose-your-own-adventure-style read that offers concrete solutions to some of life's biggest hurdles—physical, mental, emotional, or otherwise. Whether you decide to read the entire book at once for total transformation, a tip a day to add a dose of inspiration to your morning routine, or go directly to the sections that address your specific needs and challenges, every page of 100 Ways to Change Your Life offers powerful, habit-building tips across subjects ranging from mental health, careers, relationships, confidence, and physical health in 100 fun-to-read, easy-to-digest parts that provide highly actionable tools and mindset-shifting ideas that will change every part of your life—from the moment you turn the first page.